The Evaluation of Uterine Sarcomas: Tertiary Center Experience - Yavuz, Onur; Mankan, Kadir Alper; Akdoner, Asli; Ot, Sultan; Saatli, Hasan Bahadir (Gynecology Obstetrics & Reproductive Medicine, 2024)
BJECTIVES: To elucidate prognostic factors, determine the best course of treatment methods, and assess oncological results in individuals diagnosed with uterine sarcoma. STUDY DESIGN: Between January 2001 and August 2023, 30 patients with uterine sarcomas (US) were included and analyzed in this cross-sectional study. Sixteen patients (53.3%) had uterine leiomyosarcoma, 6 patients (20%) had high-grade endometrial stromal sarcoma, 8 patients (26.7%) had low-grade endometrial stromal sarcoma. RESULTS: The median follow-up of all participants was 50 months. Recurrence was detected in 43.3% of the patients. 5-year survival ratio was 73.3%, 5-year disease-free survival ratio was 66.7%, the overall survival ratio was 70% and the overall disease-free survival rate was 56.6%. No difference was observed between groups in terms of survival comparisons. No statistically significant effect of adjuvant systemic chemotherapy, adjuvant radiotherapy, and combined treatments on median overall survival and median disease-free survival was detected (p>0.05). CONCLUSION: Uterine sarcomas are uncommon malignancies characterized by a poor prognosis, even in early stages, and they are associated with a high recurrence ratio. The most effective treatment method remains unclear to date.